PERCEPTIONS OF IMPLEMENTATION OF SCHOOL ENVIRONMENT INTRODUCTION AT SMK KARSA MULYA WITH PARETO ANALYSIS - Erno Leluanto (Jurusan Pendidikan Teknologi Dan Kejuruan, 2022)
This study aims to find out the description of the perception of the implementation of the introduction of the school environment at Karsa Mulya Vocational School with Pareto Analysis and to know the response of students' understanding of the school environment with Pareto Analysis. This research is a Mixed Method Research (MMR) combining qualitative and quantitative data analysis using qualitative and quantitative data collection, so it is called Mixed Method Research (MMR). The data collection method is in the form of a questionnaire or questionnaire. Data obtained through questionnaires or questionnaires were given to 30 respondents who were randomly distributed to students. The data analysis technique used in this research is descriptive analysis. Data analysis uses a Likert scale with a score of 1 to 5, with 30 student respondents, judging by the 10 questions tabulated into percentages to see which scale must be corrected from 10 questions with Pareto analysis with the SPSS 22.0 program. The results showed that the perception of the implementation of the introduction of the school environment at SMK Karsa Mulya through five aspects of the approach, namely the preparation of lesson plans, the teaching process, extracurricular activities, relations with the school and the guidance process. Of the five aspects that need attention and improvement in the introduction of the school environment are extracurricular and relations with the school because they have a lack of response, but there are already three good aspects, namely the preparation of lesson plans, the teaching process and the guidance process. The perception of the implementation of the introduction of the school environment at Karsa Mulya Vocational School with Pareto Analysis shows that the problems that dominate the process of introducing the school environment through PPL 1 are extracurricular as many as 16 responses with a percentage of 35% and the relationship with the school as many as 12 responses with a percentage of 61% so that this problem in the future it must be improved, then for the preparation of the lesson plans, the teaching process and the guidance process provide a good value from the provision of material in PPL 1 which was responded well.